Gross efficiency and energy expenditure in kayak ergometer exercise - Gomes, B. B.; Mourao, L.; Massart, A.; Figueiredo, P.; Vilas-Boas, J. P.; Santos, A.M. C.; Fernandes, R. J. (International Journal of Sports Medicine, 2012)
We purposed to study energy expenditure, power output and gross efficiency during kayak ergometer exercise in 12 elite sprint kayakers. 6 males (age 24.2±4.8 years, height 180.4±4.8 cm, body mass 79.7±8.5 kg) and 6 females (age 24.3±4.5 years, height 164.5±3.9 cm, body mass 65.4±3.5 kg), performed an incremental intermittent protocol on kayak ergometer with V?O2 and blood lactate concentration assessment, a non-linear increase between power output and energy expenditure being observed. Paddling power output, energy expenditure and gross efficiency corresponding to VO2max averaged 199.92±50.41 W, 75.27±6.30 ml.kg - 1.min - 1, and 10.10±1.08%. Male kayakers presented higher VO2max, power output and gross efficiency at the VO2max, and lower heart rate and maximal lactate concentration than females, but no differences were found between genders regarding energy expenditure at VO2max. Aerobic and anaerobic components of energy expenditure evidenced a significant contribution of anaerobic energy sources in sprint kayak performance. Results also suggested the dependence of the gross efficiency on the changes in the amount of the aerobic and anaerobic contributions, at heavy and severe intensities. The inter-individual variance of the relationship between energy expenditure and the corresponding paddling power output revealed a relevant tracking for females (FD Gamma =0.73±0.06), conversely to the male group (FD Gamma=0.27±0.08), supporting that some male kayakers are more skilled in some paddling intensities than others.